Wearable Device for Monitoring Child Safety in Distress Situation using IoT - V.Prabhu, D. Jaganathan, R.Thiagarajan, I. Mohan, V.Balaji Vijayan, R.jothi Kumar (International Journal of Advanced Science and Technology, 2020)
In today’s current situation we see that there are many children getting kidnapped or lost. The survey states that around thousands of children are been missing every year and it is very pathetic that around ¾ are been rescued and remaining are found to be lost. To address this sort of situation a SOC (Safety of Child) wearable tracker is been proposed in this paper. It enables the information of the child to be send to parents in case if they are found to be missing. Two way of information are been passed to the parents mobile. This is a simple application which is adaptable to all sort of mobile and it is not expected to be only smart phone. The information passed about the child location, temperature, heart beat rate is send to parent mobile and finally SOS(save our soul) light and buzzer sound is raised which is heard by nearby people and child can be rescued. These information are received upon certain keywords such as LOCATION, BUZZ, HBT, TEMP etc. The second means of receiving the information is through the heart beat rate. The threshold value is been set for heartbeat sensor. In case of emergency the child heart beat rises which is been detected by the sensor and when it crosses the threshold value immediately the location and heart beat is send to parent which automatically convey that their child is in need of help. This device is helpful and is of great relief for parents to safeguard their children at all cases. Keyword: SOC Tracker, Wearable, SOS.